2013
DOI: 10.1002/jbm.a.34573
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo mechanical properties of human ulnar and median nerves

Abstract: Peripheral nerves are often subjected to mechanical stretching, which in excess results in various degrees of impairment of their function. An understanding of the biomechanical behavior of peripheral nerves is important to the prevention of nerve injury during surgical manipulation. Here, in vitro mechanical properties and viscoelastic behavior of human ulnar/median nerves were measured with a tensile tester. In vivo stress and deformation of an ulnar nerve was also examined in continuity during a surgical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 44 publications
3
43
0
Order By: Relevance
“…On the basis of the results of this study, there is a need to define the normal strains of age-specific groups. Third, we did not confirm our findings by alternative methods, such as magnetic resonance elastography (McCullough et al 2011) or other strain measurement methods (Ma et al 2013). However, there is still no gold standard for the measurement of peripheral nerve strain both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 65%
“…On the basis of the results of this study, there is a need to define the normal strains of age-specific groups. Third, we did not confirm our findings by alternative methods, such as magnetic resonance elastography (McCullough et al 2011) or other strain measurement methods (Ma et al 2013). However, there is still no gold standard for the measurement of peripheral nerve strain both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 65%
“…Human peripheral nerves are known to exhibit viscoelastic properties [16] and this has been demonstrated for the human ulnar nerve by performing in vitro stress relaxation tests [17].…”
Section: Introductionmentioning
confidence: 99%
“…Other research groups have performed studies on the mechani cal behavior and/or the microstructure of other peripheral nerves including but not limited to the ulnar nerve, tibial nerve, median nerve, and sciatic nerve [32,[42][43][44][45][46][47][48][49], Ma et al published a study of adult human cadaver ulnar nerves stretched at a rate of 0.05 mm/s up to 10% strain found an average maximum value of tensile stress to be 0.18 MPa which is lower on average than the stresses we have calculated in the porcine RLN [43], In another study of the sciatic nerve of female guinea pigs, Young's Modulus was reported at 5%, 10%, 15%, and 20% strain, being 32 MPa (±13) at 15% which is the maximum stretch we achieved in our study [46]. This is higher than the values we reported which may be due to differences in species and/or differences in the amount of force imposed on the sciatic nerve than the RLN.…”
Section: R E P R E S E N Ta Tiv E S H G M U Ltip H O T O N Im a G E Smentioning
confidence: 99%